YouTubers and Urban Everyday Narratives in Havana - Nava Contreras Nadia (Stockholm University Press, 2025)
This paper presents the first academic exploration of the Cuban YouTubesphere. It addresses the surge and momentum of digital content production publicly distributed through the YouTube platform, focusing on Havana-based creators engaging in mobile practices. These media agents feature landmarks, attractions, and quotidian itinerances portraying the city and the changes occurring within and on its representations. By juxtaposing the analysis of a large corpus of videos produced between 2017 and 2022 with netnographic and mobile ethnography observations, the article contextualizes Cuba’s YouTuber boom within the larger framework of the state-led Digital Revolution. Then, it reflects briefly on the implications of YouTubers’ (g)local narratives as 1) objects of affection for the digital diaspora and people interested in Cuba, 2) a form of public space intervention, 3) a digital repository portraying the urban quotidian amidst societal transformations.